TINJAUAN HISTORIS TEKNOLOGI VARIETAS UNGGUL DAN PROGRAM INTENSIFIKASI DALAM PENINGKATAN PRODUKTIVITAS PADI BERKELANJUTAN - Dewa K S Swastika; Adang Agustian; Achmad Suryana; Chairul Muslim; nFn Sunarsih; Resty Puspa Perdana (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
Since 1943 hundreds of superior varieties of rice have been released, but domestic rice production has not been able to meet the national rice needs. One of the main problems is the decrease in fertile land due to continuous land conversion. Therefore, the main mainstay in increasing rice production is increasing productivity through technological improvements. For this reason, Balitbangtan continues to create new high-yielding varieties of rice through plant breeding. More than 200 high-yielding varieties of rice have been produced to meet the challenge of increasing productivity. This paper aims to examine the historical profile of the creation of superior rice varieties in line with intensification programs and their role in increasing national rice production. The study was conducted using a desk study approach, which was to examine secondary data and literature from various publications. The results of the study showed that the creation of high-yielding varieties accompanied by various intensification programs has succeeded in increasing rice productivity in a sustainable manner. The challenge for Balitbangtan is the creation of new high-yielding varieties with higher yields than those currently available.